Intelligent Robotics and Applications First International Conference, ICIRA 2008 Wuhan, China, October 15-17, 2008 Proceedings, Part I - Xiong, Caihua; Huang, Yongan; Xiong, Youlun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
These two volumes constitute the refereed proceedings of the First International Conference on Intelligent Robotics and Applications, ICIRA 2008, held in Wuhan, China, in October 2008. The 265 revised full papers presented were thoroughly reviewed and selected from 552 submissions; they are devoted but not limited to robot motion planning and manipulation; robot control; cognitive robotics; rehabilitation robotics; health care and artificial limb; robot learning; robot vision; human-machine interaction & coordination; mobile robotics; micro/nano mechanical systems; manufacturing automation; multi-axis surface machining; realworld applications.
Keynote Speeches -- Robot Motion Planning and Manipulation -- Robot Control -- Cognitive Robotics -- Health Care and Artificial Limb -- Robot Learning -- Robot Vision -- Mobile Robotics -- Human-Machine Interaction and Coordination -- Erratum.
Keywords: Rehabilitation; Artificial intelligence; Computer simulation; Rehabilitation medicine; Optical data processing; Rehabilitation; Artificial Intelligence; Simulation and Modeling; Rehabilitation Medicine; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision